2022
DOI: 10.3390/insects13040351
|View full text |Cite
|
Sign up to set email alerts
|

Bemisia tabaci (Hemiptera: Aleyrodidae): What Relationships with and Morpho-Physiological Effects on the Plants It Develops on?

Abstract: Although many crops have developed several adaptation mechanisms that allow them to defend against limiting factors, some biotic and abiotic stresses may cause reversible or irreversible changes in plants. Among the biotic stresses, the whitefly Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) is probably one of the main important pests that negatively affect several vegetable crops that are grown in greenhouses. The present study evaluated its impact on the morphology and physiology of two solanaceous plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…It is well known that infestation by B. tabaci affects the quantity and quality of yields in many varieties of vegetable crops [ 55 ]. The means by which whitefly infestations exert a negative effect on horticultural species (eggplant and tomato) have also been confirmed in a recent study [ 33 ]. The findings reported here show that the presence of M. pygmaeus reduces the negative effects of the whitefly on plants [ 38 , 46 ], resulting in significantly higher values of indirect chlorophyll content, chlorophyll fluorescence, leaf area, and shoot dry weight in the PIBM condition compared with the PIB.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…It is well known that infestation by B. tabaci affects the quantity and quality of yields in many varieties of vegetable crops [ 55 ]. The means by which whitefly infestations exert a negative effect on horticultural species (eggplant and tomato) have also been confirmed in a recent study [ 33 ]. The findings reported here show that the presence of M. pygmaeus reduces the negative effects of the whitefly on plants [ 38 , 46 ], resulting in significantly higher values of indirect chlorophyll content, chlorophyll fluorescence, leaf area, and shoot dry weight in the PIBM condition compared with the PIB.…”
Section: Discussionmentioning
confidence: 76%
“…This study considered the principal morphological and physiological traits (e.g., plant height, dry plant biomass, chlorophyll content, etc.) [ 33 ] and found that eggplant and tomato plants infested by the whitefly showed strong and significant reductions in height, shoot dry weight, leaf area, and indirect chlorophyll content, though with different levels of intensity among the two plant species. Starting from the above results, and in order to widen our knowledge of multitrophic interaction mechanisms related to the impact of whiteflies on plant biology, a further trophic level in the analysis was added.…”
Section: Introductionmentioning
confidence: 99%
“…The reduced levels of chlorophyll may be because of sucking on plant sap containing plant pigments. Due to the lowering level of chlorophyll content as a result of B.tabaci feeding compatible with (19,20) who mentioned that the concentration of chlorophyll changes in the plant during its growth or as a result of external pressure, such as infestation with sup-sucking insects that feed on plants sap 21,23 .…”
Section: Discussionmentioning
confidence: 92%
“…Where D represents the spectrophotometer reading, 20.2 and 8.02 mg/g referred to the absorbance of chlorophyll a and b at 645 nm and 663 nm, respectively. % reduction of chlorophyll was calculated by the equation below as described by Farina et al 23 :…”
Section: Chlorophyll Contentmentioning
confidence: 99%
“…Bemisia tabaci is a global sap‐sucking insect pest causing severe damage to many agricultural crops and ornamental plant species (De Barro et al, 2011; Farina et al, 2022). The taxonomy of B. tabaci is an ongoing area of research, with the current consensus being that it represents a cryptic species complex consisting of over 40 morphologically indistinguishable species (Dinsdale et al, 2010; Tay et al, 2012).…”
Section: Introductionmentioning
confidence: 99%